Study and Analysis of AI and Fintech on Quality of Accounting Information Disclosures and Corporate Governance with special reference to Banking Sector - Sharad Kelkar , Abhijit (International Journal of Computational and Experimental Science and Engineering, 2025)
The rapid integration of Artificial Intelligence (AI) and Financial Technology (Fintech) in the banking sector has significantly enhanced the quality of accounting information disclosures and corporate governance. AI-driven automation, machine learning, and Fintech innovations such as blockchain, smart contracts, and real-time data analytics have improved financial transparency, accuracy, and compliance. These technologies minimize human errors, detect fraud, and strengthen risk assessment processes, ensuring more reliable financial reporting. AI-powered audits and predictive analytics enhance corporate governance by promoting accountability, regulatory compliance, and investor confidence. However, the adoption of AI and Fintech also presents challenges such as cybersecurity risks, algorithmic biases, ethical concerns, and evolving regulatory frameworks. This study aims to analyze the impact of AI and Fintech on financial disclosures and governance structures in banking institutions, exploring both the opportunities and risks associated with their implementation. The findings provide insights into how AI-driven technologies can revolutionize financial reporting and governance while maintaining transparency and sustainability